2022
DOI: 10.29333/ejmste/12245
|View full text |Cite
|
Sign up to set email alerts
|

Argumentative orchestration in the mathematical modelling cycle in the classroom

Abstract: Given the importance of modelling in mathematics classrooms, and despite the extensive body of research on teacher support for promoting the mathematical modelling cycle in the classroom, authors have overlooked how teacher support for argumentation can contribute to this cycle. This study is aimed at characterizing teacher support for argumentation in the mathematical modelling cycle in the classroom. We analyzed 10 class episodes taken from the cases of two teachers, Soledad and Ángeles. The episodes were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…An innovative aspect of this research is that we inferred the knowledge and beliefs based on the argumentation of the prospective teacher studied, which we analyzed from unusual theoretical references, namely, from the pragma-dialectical perspective [33] for the analysis of a critical discussion through four stages (confrontation, opening, argumentation, and concluding stages); and from the diagramming technique [34], which allows, on one hand, to make a spatial map of the argumentation, considering the language and, on the other hand, to shape the written reasoning. In the literature review, we have not found works that infer prospective teachers' knowledge and beliefs from the analysis of the structure of the argumentation, which they realize when they reflect on their practice, with models other than Toulmin's [35] (among others, the works of [36,37]). Similarly, unlike the research commented in the literature review [23][24][25][26][27][28][29], where knowledge and beliefs are extracted through the application of questionnaires and interviews with items aimed at individuals clearly expressing their knowledge and beliefs; in this study, we opted for argumentation as a means to infer these elements indirectly.…”
mentioning
confidence: 99%
“…An innovative aspect of this research is that we inferred the knowledge and beliefs based on the argumentation of the prospective teacher studied, which we analyzed from unusual theoretical references, namely, from the pragma-dialectical perspective [33] for the analysis of a critical discussion through four stages (confrontation, opening, argumentation, and concluding stages); and from the diagramming technique [34], which allows, on one hand, to make a spatial map of the argumentation, considering the language and, on the other hand, to shape the written reasoning. In the literature review, we have not found works that infer prospective teachers' knowledge and beliefs from the analysis of the structure of the argumentation, which they realize when they reflect on their practice, with models other than Toulmin's [35] (among others, the works of [36,37]). Similarly, unlike the research commented in the literature review [23][24][25][26][27][28][29], where knowledge and beliefs are extracted through the application of questionnaires and interviews with items aimed at individuals clearly expressing their knowledge and beliefs; in this study, we opted for argumentation as a means to infer these elements indirectly.…”
mentioning
confidence: 99%